Obstetric Outcomes in Young Women with Breast Cancer: Prior, Postpartum, and Subsequent Pregnancies - Ma, Kimberly K.; Preusse, Courtney J.; Stevenson, Philip A.; Winget, Veronica L.; McDougall, Jean A.; Li, Christopher I.; Gadi, Vijayakrishna K.; Gammill, Hilary S. (American Journal of Perinatology, 2020)
Objective This study aimed to describe obstetric outcomes in a large cohort of young women with breast cancer, considering the chronological relationship of pregnancies with breast cancer diagnosis.Study Design From a population-based cohort study of young women with breast cancer from 2004 to 2010, we conducted secondary interviews to obtain detailed obstetric histories. Pregnancies were categorized based on timing of breast cancer diagnosis: prior, postpartum, and subsequent pregnancies after breast cancer diagnosis. A generalized estimated equation model was used to account for correlated data.Results In this cohort (n = 366), median age at breast cancer diagnosis was 40.1 years, and 84.7% were Caucasian. Tumor type was notable for 25.1% triple negative, and 56.1% had Stage I disease. There were 922 prior pregnancies, 21 with postpartum diagnosis of breast cancer, and 24 pregnancies subsequent to breast cancer diagnosis. Non-live birth outcomes occurred significantly more often in the postpartum group (p-value: 0.001) compared with the other groups, which had higher live birth rates, after adjustment for maternal age, parity, body mass index, and race.Conclusion Overall, pregnancy outcomes before and after breast cancer diagnosis are reassuring.
Keywords: breast cancer; pregnancy; obstetric outcomes